The effect of substitution rare earth metal on crystal structure and properties of quaternary La4-4xR4xGe3S12 (R – Er, Ho, Y, Dy, Tb) sulfide - Smitiukh, O.; Marchuk, O. (Physics and Chemistry of Solid State, 2024)
Establishing relationships between the distribution of atoms in a crystalline unit cell and the properties of phases is an important issue directly related to the application of functional materials. In this work, we present an analysis of the crystalline structure, chemical bonds, and prediction of material properties using the example of tetragonal phases La4-4xR4xGe3S12 (R - Er, Ho, Y, Dy, Tb), which crystallize in space group R3c. The presence of rare earth elements with high coordination in the first coordination sphere is a significant contribution to changing properties, particularly thermoelectric properties. This creates the possibility of increasing the entropy factor and, as a result, improving the thermoelectric characteristics. The parameters of the elementary cell of the initial ternary phase La4Ge3S12 decrease at a ratio of 1La:1R (R - Tb, Dy, Ho, Er) in the site 6a and 18b. In the Er-containing phase, the lowest distortion index for the [M1 8S] polyhedron, while in the [M1 9S] polyhedron it significantly increases. Additionally, the formation of "columns" from polyhedra [Ge2 6S] creates the possibility of directional excitation in one direction, which can also have a significant impact on material properties. Overall, the obtained non-symmetric materials may be promising for nonlinear optics.